Guide to the European Union 2001-2002 : an overview of current issues - Rousselot-Pailley, Gérard (Roupater BrusselsBE, 2002)
Focuses on aspects such as: institutional affairs; the European economy over the 2001-2002 period; development of common policies; and, the European Union's neighbours.